2020
DOI: 10.3390/su12030920
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Perception of Local Extra Virgin Olive Oil and Consumers’ Attitude: A New Italian Perspective

Abstract: Extra virgin olive oil sustainability shows that it is strictly connected to local production and certifications. However, consumers’ behaviour toward a local product is tied with the information exchange between producers and consumers. The aim of the research is to analyse, using a logistic regression model, if the attitudes, habits, and behaviours of the consumers influence their opinion on the sustainability of local extra virgin olive oil, relative to the three dimensions of sustainability (environmental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 118 publications
1
16
0
Order By: Relevance
“…These answers show a good knowledge and consumer attitudes towards organic and geographical indication certifications of EVOO. These results share a number of similarities with those of Polenzani et al [ 90 ], who associate traditional consumption of EVOO and general knowledge of the product and its main attributes.…”
Section: Resultssupporting
confidence: 86%
“…These answers show a good knowledge and consumer attitudes towards organic and geographical indication certifications of EVOO. These results share a number of similarities with those of Polenzani et al [ 90 ], who associate traditional consumption of EVOO and general knowledge of the product and its main attributes.…”
Section: Resultssupporting
confidence: 86%
“…Consumer's behavior, however, is tied to information exchange between consumer and other supply chain participants. The development of blockchain technology-based solutions to improve this information exchange from a managerial and political point of view shall lead to the prevention of fraud [51]. Table 6 shows the distribution of the research papers in this category.…”
Section: Anti-counterfeitingmentioning
confidence: 99%
“…The locality of the organic food supply could potentially off-set the high price concern linked to organic foods. Consumers believe that locally produced greens produce a smaller carbon-footprint and are thus more environmental friendly and sustainable [59,60]. Timmins [12] found that 60% of his respondents were interested in locally sourced crops.…”
Section: Perceived Qualitymentioning
confidence: 99%